انعكاس سعر الصرف على التضخم في الاقتصادیات الناشئة - سیداحمد زناقي; مریم حسناوي (Finance and Business Economies Review, 2018)
The paper is a summary of a research in Pass-through exchange rate, that has taken a great part in the writings of international finance by measuring the impact of the exchange rate reflection on domestic prices. It is partly partial and total, which affects the channels of transfer between countries through commercial transactions or capital movement. The determinants of reflection are: structure and level of competition in market, inflationary environment, economic activity, real exchange rate, degree of trade openness, exchange rate systems, citing a series of empirical studies and measurement results in developing countries. Reflections are represented in Taylor 2000, Edwards 2006.